2007
DOI: 10.1111/j.1600-0447.2006.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin level during 5 years of risperidone treatment in patients with psychotic disorders

Abstract: Risperidone induces a higher prolactin elevation than other atypical antipsychotics, but the effect adapts over time. Prolactin was not associated with expected side effects (e.g. sexual, mental, or weight gain).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
3
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 40 publications
2
37
3
4
Order By: Relevance
“…Many if not all of the data are of too short a duration to make definitive statements regarding the persistence of hyperprolactinemia during treatment with antip sychotics [Bushe et al 2008]. However, there is a 5year naturalistic study of risperidone that suggests that prolactin levels may decrease over time [Eberhard et al 2007]. In the present study we observed a significant increase in prolactin levels both in women and men in concordance with the literature data.…”
Section: Discussionsupporting
confidence: 89%
“…Many if not all of the data are of too short a duration to make definitive statements regarding the persistence of hyperprolactinemia during treatment with antip sychotics [Bushe et al 2008]. However, there is a 5year naturalistic study of risperidone that suggests that prolactin levels may decrease over time [Eberhard et al 2007]. In the present study we observed a significant increase in prolactin levels both in women and men in concordance with the literature data.…”
Section: Discussionsupporting
confidence: 89%
“…27 The most common adverse events after the use of AAP were two: drowsiness and weight gain. Risperidone was more frequently associated with increases in prolactin levels, 40 and the use of ziprasidone was only partially associated with weight gain. 52 Data about quetiapine and aripiprazole are still too limited to provide a minimally consistent evaluation of their adverse events.…”
Section: Risperidonementioning
confidence: 98%
“…39 The comparison with other AAPs revealed that risperidone was the medication that resulted in the highest prolactin elevation among adults with schizophrenia (n = 218) in a study that followed up patients for five years. 40 In a study that compared the use of olanzapine with that of haloperidol in 12 children with autism for six weeks, olanzapine was more efficacious in the control of aggression, but resulted in greater weight gain. 44 In some emergency situations that require aggression control, the IM injection of a rapid-acting medication may be necessary.…”
Section: Risperidonementioning
confidence: 99%
“…The course and persistence of HPL in relation to antipsychotic use overtime remains a complex question, and one with which the literature is limited by a lack of prospective studies (Eberhard et al, 2007;Pérez-Iglesias et al, 2012). However, our naturalistic study provides further evidence that rates of HPL do decline over the first year of illness, but that HPL persists with all antipsychotics used, with higher rates of sustained HPL seen with amisulpride, risperidone and FGAs.…”
Section: Antipsychotics and Hplmentioning
confidence: 74%